Nutrient biomass production from agro-industrial residues using Yarrowia lipolytica: screening and optimization of growing conditions - Thiago Bergler Bitencourt; Fernanda Arpini Souza; Vanessa Gomes da Silva; Edmilson José Kleinert; André Martins (Brazilian Journal of Food Technology, 2022)
Abstract The possibility of using agro-industrial residues in bioconversion processes advances with the development of biotechnology and the search for processes in which is possible to add commercial value to previously discarded products. These processes should be low cost, easy to control and chemical-free. The yeast Yarrowia lipolytica (YL) is widely used to produce lipids, enzymes, citric acid, and proteins, among others. This study aimed to evaluate the capacity of this yeast to use agro-industrial residues as a source of carbon without adding extra carbohydrate sources for the development of cells. The study evaluated the production of proteins and lipids from different carbon sources as well as the optimization of the process (agitation, temperature, and nitrogen source). Indeed, YL produced 22.3% of protein and 9.4% of lipids in dry biomass, a 179% of protein and 660% of lipid increase from raw material, respectively, when using cassava residues as a carbon source. However, lipase production was low, indicating that the strain had priority for cell growth.